Urgensi Pengaturan Sanksi bagi Perusahaan yang Tidak Melaksanakan Corporate Social Responsibility - Rahmania, Auliya (Universitas Ekasakti, 2023)
One of the company's obligations is to carry out a corporate social responsibility (CSR) program, where this obligation contains sanctions for companies that do not carry out CSR. The aim of this research is to determine the urgency of regulating sanctions for companies that do not implement Corporate Social Responsibility (CSR) in Indonesia. The research method used is normative legal research which is carried out to look for legal problems or issues and existing legal problems. The research results show that the urgency of regulating sanctions for companies that do not implement TJSL, which departs from the basic understanding that the implementation of TJSL which is a legal obligation (legal mandatory) basically confirms that TJSL is no longer interpreted as voluntary, but as a legal obligation ( legal mandatory) to be implemented.